2021
DOI: 10.3390/molecules26040802
|View full text |Cite
|
Sign up to set email alerts
|

Positive Effect of Cannabis sativa L. Herb Extracts on Skin Cells and Assessment of Cannabinoid-Based Hydrogels Properties

Abstract: The skin is an organ that is constantly exposed to many external factors that can affect its structure and function. Due to the presence of different cannabinoid receptors on many types of skin cells, cannabinoids can interact directly with them. Therefore, as part of this work, the impact of two types of Cannabis sativa L. herb extracts on keratinocytes and fibroblasts was assessed. The content of biologically active compounds such as phenols, flavonoids, chlorophylls and cannabinoids was evaluated. The antio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 61 publications
3
30
0
Order By: Relevance
“…Another essential substance in plant extracts is the assimilation pigments. Chlorophyll may also enhance the antioxidant properties [ 44 ]. In our study, we showed the total polyphenol and flavonoids and the assimilation pigments contents in FEE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another essential substance in plant extracts is the assimilation pigments. Chlorophyll may also enhance the antioxidant properties [ 44 ]. In our study, we showed the total polyphenol and flavonoids and the assimilation pigments contents in FEE.…”
Section: Discussionmentioning
confidence: 99%
“…The hydrogel was prepared according to a modified procedure by Zagórska-Dziok et al [ 44 ]. Sequentially, an aqueous solution of hydroxyethyl cellulose (HEC) was prepared.…”
Section: Methodsmentioning
confidence: 99%
“…The simple and effective topical administration of cannabinoids on skin lesions is helpful not only in ensuring substance delivery to the inflammation site but also in observing local adverse effects [154]. The additional anti-aging, anti-oxidative and antitumoral effects provide supplementary benefits in the use of cannabinoids in other diseases that are associated with inflammation, including cancer [155,156]. However, many of the studies are preclinical, and there are very few trials free of bias with a large enough number of participants to be considered high-quality [157].…”
Section: Cannabinoids and Inflammatory Skin Disordersmentioning
confidence: 99%
“…Recently, cannabis extracts, and CBD in particular, have also gained tremendous attention in the cosmetic industry sector owing to their moisturizing, anti-aging, anti-inflammatory, antioxidant and cytoprotective properties [5,6]. Moreover, recent studies have shown that cannabis extracts do not lead to cytotoxic effects on keratinocytes and skin fibroblasts, proving the safety and non-irritancy of cannabis active ingredients [7,8]. CBD is a highly lipophilic drug (log P = 6.3) and, therefore, it is frequently incorporated in alcohol-based formulations or oils [9].…”
Section: Introductionmentioning
confidence: 99%